The Challenges Of Implementation Of Professional Teachers Competency In The Digital Era - Hartoyo, Joko; Ahmad, Syarwani; Fitriani, Yessi (Jurnal Pendidikan Tambusai, 2021)
Teachers are required to keep up to developments in information and communication technology as educators. It is a challenge for teachers to maintain their professional competence in achieving national education goals in this digital era. This research aims to study the implementation in the digital era of teacher professional competence. This research utilizes qualitative methods.